Synthesis of Squaric Acid Monoamides as Building Blocks for Drug Discovery - Long, Nathan; Le Gresley, Adam; Solomonsz, Arran; Wozniak, Antony; Brough, Steve; Wren, Stephen P. (SynOpen, 2023)
Herein, we present a synthetic compound library comprising of 28 anilino and benzylamino monosquarate-amide derivatives. Members of this library were designed as bioisosteric replacements for groups such as the ubiquitous carboxylic acid moiety. Further to their synthesis, we have shown the potential of these chemical building blocks for the generation of additional novel compounds. This work forms part of our efforts aimed at the assembly of 96-well plates loaded with bioisosteric analogues that may be used to enrich drug discovery programs. The research presented in this work focuses on the chemistry of 3,4-dihydroxycyclobut-3-ene-1,2-dione, a known carboxylic acid bioisostere.
Keywords: squaric acid; squaramide; bioisostere; carboxylic acid; compound library